2009
DOI: 10.1038/npp.2009.144
|View full text |Cite
|
Sign up to set email alerts
|

The Glycine Transporter-1 Inhibitor SSR103800 Displays a Selective and Specific Antipsychotic-like Profile in Normal and Transgenic Mice

Abstract: Schizophrenia has been initially associated with dysfunction in dopamine neurotransmission. However, the observation that antagonists of the glutamate N-methyl-D-aspartate (NMDA) receptor produce schizophrenic-like symptoms in humans has led to the idea of a dysfunctioning of the glutamatergic system via its NMDA receptor. As a result, there is a growing interest in the development of pharmacological agents with potential antipsychotic properties that enhance the activity of the glutamatergic system via a modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 54 publications
(76 reference statements)
2
18
0
1
Order By: Relevance
“…dose-dependently suppressed hyperlocomotion in DAT −/− mice (Fig. 5C) similar to classical (haloperidol) and atypical (olanzapine and clozapine) antipsychotics (27). This finding further indicates that at least this effect of TAAR1 activation on DA-related function is independent of DAT.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…dose-dependently suppressed hyperlocomotion in DAT −/− mice (Fig. 5C) similar to classical (haloperidol) and atypical (olanzapine and clozapine) antipsychotics (27). This finding further indicates that at least this effect of TAAR1 activation on DA-related function is independent of DAT.…”
Section: Resultssupporting
confidence: 59%
“…Instead, we found that RO5166017 displays psychoactive properties in mice. Selective TAAR1 activation reduced anxiety in the SIH paradigm and fully prevented psychostimulant-induced and persistent hyperdopaminergia-related hyperactivity similar to the antipsychotic drug olanzapine (27). Importantly, these effects were not observed in Taar1 −/− mice, showing that the anxiolytic-and antipsychotic-like properties of RO5166017 result from selective activation of TAAR1.…”
Section: Discussionmentioning
confidence: 80%
“…For example, in male CD-1 mice, clozapine failed to reverse MK-801-induced PPI deficit at lower doses (0.1 and 0.3 mg/kg; Curzon and Decker 1998), while at higher dose (3.0 mg/kg) it reserved PPI deficit exhibited by dopamine transporter knockout mice (Powell et al 2008). Also, in female TO mice, haloperidol inhibited MK-801-induced hyperactivity only at a dose (0.1 mg/kg) that also attenuated spontaneous activity , whereas in male Swiss mice a higher dose (0.3 mg/ kg) reduced MK-801-induced hyperactivity without affecting spontaneous activity (Boulay et al 2010). …”
Section: Introductionmentioning
confidence: 79%
“…GlyT-1 inhibitors are effective in most rodent models of schizophrenia associated with alterations in NMDA transmission (Alberati et al, 2011;Boulay et al, 2010;Yang et al, 2010). GlyT-1 inhibitors have also been reported to alleviate some of the ketamine-induced behavioural and cognitive disturbances in nonhuman primates (Roberts et al, 2010b) and in humans (D'Souza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%